2014
DOI: 10.2134/fg-2014-0006-rs
|View full text |Cite
|
Sign up to set email alerts
|

Inoculants to Enhance the Ruminal Degradation of Small‐Grain Forage

Abstract: Fibrolytic enzymes and microbial inoculants have the potential to improve fiber degradability. A 2 × 2 × 2 factorial experiment was conducted to determine the nutritive value, ruminal degradability, and degradation rates of wheat (Triticum aestivum L.) and oat (Avena sativa L.) pretreated with fibrolytic enzyme (xylanase plus cellulase: XC) or bacterial [Promote ASB (Lactobacillus buchneri and L. plantarum); PRO] inoculants at two maturities. Forage was harvested twice during the tillering stage (H1 and H2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The AP silage treated with LAB inoculants had lower contents of fibre fractions and fat, which might be the reason for improved DM degradation of the silage compared to the untreated silage. This enhanced rumen degradation rates of DM indicate that the LAB inoculants (EMS and Sil) may have increased the available energy to rumen microbes (Thomas-Moen et al, 2014). However, the nonresponse of LAB inoculation to the undegradable DM fractions of the AP silage contradicts the findings of Thomas-Moen et al (2014) who reported reduced undegradable fractions with LAB inoculation to either wheat or oat forages.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The AP silage treated with LAB inoculants had lower contents of fibre fractions and fat, which might be the reason for improved DM degradation of the silage compared to the untreated silage. This enhanced rumen degradation rates of DM indicate that the LAB inoculants (EMS and Sil) may have increased the available energy to rumen microbes (Thomas-Moen et al, 2014). However, the nonresponse of LAB inoculation to the undegradable DM fractions of the AP silage contradicts the findings of Thomas-Moen et al (2014) who reported reduced undegradable fractions with LAB inoculation to either wheat or oat forages.…”
Section: Discussionmentioning
confidence: 90%
“…This enhanced rumen degradation rates of DM indicate that the LAB inoculants (EMS and Sil) may have increased the available energy to rumen microbes (Thomas-Moen et al, 2014). However, the nonresponse of LAB inoculation to the undegradable DM fractions of the AP silage contradicts the findings of Thomas-Moen et al (2014) who reported reduced undegradable fractions with LAB inoculation to either wheat or oat forages. This suggests that LAB could differently affect ruminal degradability of different roughages.…”
Section: Discussionmentioning
confidence: 90%
“…With modeling, IV and IS techniques can bring together measures of fiber, which are laboratory measures, to in vivo apparent digestibility and intake, which are animal-influenced measures, as a proxy to expensive and time- and labor-consuming feeding trials, which require much larger amounts of feedstuffs and more animal experimental units. Ranking of IV or IS results can help determine forages in breeding programs that are most suitable for advancement ( Foster et al, 2007 ), impact of genetic traits on potential animal performance ( McCuistion et al, 2017 ), the ideal maturity stage for harvest ( Foster et al, 2012 ), harvested forage preservation method ( Foster et al, 2011 , 2012 ), harvested forage preservation aids such as enzyme or microbial applications before ensiling ( Thomas et al, 2013 , 2014 ; McCuistion et al, 2017 ; Foster et al, 2019 ), alternative uses of row crop residues ( Foster et al, 2012 , 2019 ), supplementation regimes ( Smith et al, 2017 ), and among many other applications.…”
Section: Introductionmentioning
confidence: 99%